Cálculo y mapeo de la radiación solar directa y difusa en Costa Rica (ING) - Wright, Jaime (2008)
Knowledge of direct and diffuse solar radiation in the area is vital importance for the use of solar energy, since it is a prerequesite information for the assessment and design of solar energy system. The work presented here focus on calculation and plotting of contours values of direct and diffuse solar radiation maps based on sixty two scattered radiometric stations nation wide. In the plotting of these contours experimental and predicted values are used, these are compared with the period of dry and rainy season into the six main climate regions of Costa Rica: Central Valley, North Pacific, Central Pacific, South Pacific, North Zone and Caribbean Region. The observed daily mean levels of direct solar radiation oscillate between 6.1 and 10.1 MJ/m2 with higher values in the North Pacific, western part of the Central Valley and in the tops of the highest mountains. The lowest values agree with the North Zone and the Caribbean Region. The highest values of diffuse solar radiation agree with the North Zone and the South Pacific. It is observed an increase of 40% of the direct radiation during dry season months.